Modulation of Macrophages Using Nanoformulations with Curcumin to Treat Inflammatory Diseases: A Concise Review - Huxiao Sun; Mengsi Zhan; Serge Mignani; Dzmitry Shcharbin; Jean-Pierre Majoral; João Rodrigues; Xiangyang Shi; Mingwu Shen (MDPI AG, 2022)
Curcumin (Cur), a traditional Chinese medicine extracted from natural plant rhizomes, has become a candidate drug for the treatment of diseases due to its anti-inflammatory, anticancer, antioxidant, and antibacterial activities. However, the poor water solubility and low bioavailability of Cur limit its therapeutic effects for clinical applications. A variety of nanocarriers have been successfully developed to improve the water solubility, in vivo distribution, and pharmacokinetics of Cur, as well as to enhance the ability of Cur to polarize macrophages and relieve macrophage oxidative stress or anti-apoptosis, thus accelerating the therapeutic effects of Cur on inflammatory diseases. Herein, we review the design and development of diverse Cur nanoformulations in recent years and introduce the biomedical applications and potential therapeutic mechanisms of Cur nanoformulations in common inflammatory diseases, such as arthritis, neurodegenerative diseases, respiratory diseases, and ulcerative colitis, by regulating macrophage behaviors. Finally, the perspectives of the design and preparation of future nanocarriers aimed at efficiently exerting the biological activity of Cur are briefly discussed.